Bronchoscopy of Lung Cancer. Issue 1 (1994) - Hauck, R. W.; Emslander, H. P.
Abstract : Lung cancer is a leading cancer site in men and women with a high incidence and mortality rate. Most patients are diagnosed when the disease has already spread. An early, detection and immediate and accurate histological or cytological diagnosis are essential for a hopeful outcome. In most patients, bronchoscopy is the method of choice in establishing a suspected lung neoplasm. With the rigid and flexible method, two complementary techniques are available. The methods bear a very low mortality rate if sufficient monitoring and resuscitative instrumentation is available. Rigid bronchoscopy offers the possibility of obtaining large biopsy specimens from the tumorous tissue and provides an effective tool in the control of major haemorrhage. However, it cannot be used for the inspection of further peripherally located parts of the bronchial system and needs general anaesthesia. In contrast, the flexible method can be quickly and readily performed at practically any location using portable equipment. Bronchi can be inspected up to the 8th order and with bronchial washing, forceps biopsy, brush biopsy and fluorescence bronchoscopy techniques with a high diagnostic yield are available. This holds true, especially if these sampling techniques are used as complementary methods.